Effects of Exonuclease Activity and Nucleotide Selectivity of the Herpes Simplex Virus DNA Polymerase on the Fidelity of DNA Replication In Vivo - Hwang, Ying T. (American Society for Microbiology, 1999)
A mutagenesis system was developed for the in vivo study of the fidelity of DNA replication mediated by wild-type herpes simplex virus type 1 (HSV-1) strain KOS and its polymerase (Pol) mutant derivatives PAA(r)5, Y7, and YD12. The pHOS1 shuttle plasmid, which contained the SupF mutagenesis marker gene and the HSV ori(s) sequence, was used for analysis of the mutation frequency and the mutation spectrum. All three Pol mutants induced significant increases in the mutation frequencies of the target gene, despite the fact that PAA(r)5 was previously shown to have an antimutator phenotype by the thymidine kinase mutagenesis assay (J. D. Hall, D. M. Coen, B. L. Fisher, M. Weisslitz, S. Randall, R. E. Almy, P. Gelep, and P. A. Schaffer, Virology 132:26–37, 1984; C. B. C. Hwang and J.-H. Chen, Gene 152:191–193, 1995). Altered spectra of mutated target genes induced by these three mutants were also observed. The relative frequencies of both deletion and complex mutations found in mutants induced by exonuclease-proficient Pols were significantly higher than those induced by exonuclease-deficient Pols. On the other hand, the exonuclease-deficient Pols induced significant increases in the frequency of base substitutions, which comprised predominantly G · C-to-T · A transversions, as well as mutations at additional hot spots. These results suggest that the HSV-1 DNA Pol can incorporate purine-purine or pyrimidine-pyrimidine mispaired bases which may be preferentially proofread by its intrinsic exonuclease activity. Furthermore, the effects of the sequence context of the target gene and the assay method should also be considered carefully in any analysis of replication fidelity.